Variasi Pertumbuhan Tanaman Merbau (Intsia Bijuga O. Ktze) Hasil Stek Pucuk dari Beberapa Populasi pada Daerah Kering - Pudjiono, Sugeng (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The purpose of the study is to know the plant growth merbau by vegetative propagation of shoot cutting from 12 populations at dry areas of Gunung Kidul Yogyakarta. Twelve of these populations originated from Carita Banten, West Java, Mandopi Papua, Minamin East Halmahera Maluku, Nabire Papua, Nusajaya Halmahera Maluku, Oransbari Papua, Pacific land race Darmaga Bogor West Java, Twanwawi Papua, Waigo Papua, Wasior Papua, Seram Maluku. The design of RCBD with 12 populations consisted of totally 120 mother trees, 5 blocks, 3 treeplot, 6m x 2m trunk. The caracter traits measured were plant height, diameter of plant and survival rate at 2,5 years old. The result of varian analisis showed there are significant differences among populations that are tested on height, diameter and survival rate. From the result of research that the Pacific land race Darmaga Bogor West Java is the best growth on height 81,4cm and diameter 8,9mm. The highest of survival rate is from Oransbari Papua 82,72%. Average plant height growth Merbau at the site of the study is 61,3cm, the mean diameter 7,8mm and survival rate 63,55%.